Kajian Tarif Impor dan Kinerja Kebijakan Harga Dasar terhadap Daya Saing di Pasar Dunia - Qomarudin - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The tariff setting seems vary with large or small countries. It contributes to additional source of government revenue to finance the useful social project. Flexible import tariff setting matched with rupiah exchange rate must be important to determine the base price of product or the price of product supply. The application of import excise policy instrument has been relevant to stimulate producer to make a product. Import excise needs to be carefully designed and realistic to relieve the consumers from burdens. Base Price Policy should be higher from import parity price to cause recently improvement of Indonesia import. In other spot, import tariff policy persuades importer to consider ”moral hazard” by committing the smuggling and documentary manipulation such that data do not correspond with the reality. A key to compete within free competitive market in the liberalization era will be efficiency in which the product can be equipped with comparative and competitive strengths. It must be just appropriate to have Indonesia to drive forward the products with competitive or comparative capabilities throughout the world, and therefore, the domestic production should be pushed into worldwide market.Keywords: import tariff, base price performance, worldwide competition